Ethylene-Vinyl Acetate Copolymer/Crude Gossypol Compositions as Pour Point Depressants for Waxy Oil - Bekaidar T. Marenov; Kazim S. Nadirov; Manap K. Zhantasov; Rashid K. Nadirov (International Journal of Chemical Engineering)
Wax deposition from crude oil that blocks the pipeline and increases the viscosity of the fluid is considered as a serious challenge for petroleum transportation. Employment of chemical additives, the so-called pour point depressants (PPDs), is widely used to solve this problem. Among them are the ethylene-vinyl acetate (EVA) copolymers (EVAc), containing a polyethylene segment along the backbone with vinyl acetate. To improve the performance of EVAc as PPD, the compositions of this polymer with crude gossypol (CG), isolated from the refined cottonseed oil soapstock, were prepared by joint milling in a ball mill. Prepared compositions were characterized by Fourier transform infrared (FTIR), ultraviolet (UV), and nuclear magnetic resonance (NMR) spectroscopy. The pour point and viscosity of the crude oil from the Akshabulak oil field (Kazakhstan) were studied. The compositions with 10, 20, and 25 wt% of CG demonstrate better efficiency as PPD for crude oil than EVAc at the dosage of PPD of 50, 100, 250, and 500 ppm. The improved properties of the obtained PPD in comparison with the commercial EVAc is explained by the appearance of additional nonpolar and polar groups caused by the formation of the EVAc/CG composition.